2021
DOI: 10.3892/mmr.2021.11999
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of chaperone‑mediated autophagy reduces tumor growth and metastasis and promotes drug sensitivity in colorectal cancer

Abstract: Chaperone-mediated autophagy (CMA) is a selective type of autophagy whereby a specific subset of intracellular proteins is targeted to the lysosome for degradation. The present study investigated the mechanisms underlying the response and resistance to 5-fluorouracil (5-FU) in colorectal cancer (CRC) cell lines. In engineered 5-FU-resistant CRC cell lines, a significant elevation of lysosome-associated membrane protein 2A (LAMP2A), which is the key molecule in the CMA pathway, was identified. High expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…The result showed that CMA is a promising predictor of chemosensitivity to 5‑FU treatment and anti‑CMA therapy may be a novel therapeutic option for patients with colorectal cancer. 41 A similar study was also done and showed that inhibiting CMA activity in breast tumor cells can be exploited as a potential therapeutic application in the treatment of breast cancer. 49 Considering the physiological anti-oncogenic role of CMA, there is general agreement that preventive interventions should aim at restoring CMA activity to that in healthy conditions.…”
Section: Targeting Cma For Neurodegenerative Diseases and Cancer Therapymentioning
confidence: 82%
See 2 more Smart Citations
“…The result showed that CMA is a promising predictor of chemosensitivity to 5‑FU treatment and anti‑CMA therapy may be a novel therapeutic option for patients with colorectal cancer. 41 A similar study was also done and showed that inhibiting CMA activity in breast tumor cells can be exploited as a potential therapeutic application in the treatment of breast cancer. 49 Considering the physiological anti-oncogenic role of CMA, there is general agreement that preventive interventions should aim at restoring CMA activity to that in healthy conditions.…”
Section: Targeting Cma For Neurodegenerative Diseases and Cancer Therapymentioning
confidence: 82%
“… 3 CMA is activated in a variety of cancers, including breast, colorectal, gastric, and liver cancer, indicating that LAMP2A overexpression promotes tumor growth and metastasis. 41 CMA up-regulation may play a role in cancer pathology development. CMA’s role in promoting cancer cell survival has been linked to several mechanisms, including preventing cells from entering an apoptotic state, providing general protection against oxidative stress, and protecting pro-oncogenic proteins from degradation by other pathways.…”
Section: Pathogenic Implication Of Cmamentioning
confidence: 99%
See 1 more Smart Citation
“…EVA1A promoted oxaliplatin resistance of HCC by inducing autophagy [ 52 ]. Autophagy has been reported to promote cancer drug resistance [ 53 ], and also the strengthened drug sensitivity of cancer [ 54 ]. The above self-contradictory report may be related to the type of cancer or drug.…”
Section: The Role Of Eva1a In Hepatocellular Carcinomamentioning
confidence: 99%
“…For a protein to be selectively degraded via the CMA pathway, it needs to have the pentapeptide motif of KFERQ in its protein sequence [382]. CMA has been shown to participate in both physiological and pathological situations, including the cell cycle, maintaining hematopoietic stem-cell function, aging, neurodegenerative diseases, and cancers [383][384][385][386][387][388][389]. CMA is also regulated at different levels, from cell membrane proteins to chaperone proteins in the cytoplasm, through Lamp2a, Hsc70, GFAP, EF1α, and the mTORC2/PHLPP1/Akt signaling axis [390][391][392].…”
Section: Chaperone-mediated Autophagymentioning
confidence: 99%